Racial Disparities in Sleep: Associations With Discrimination Among Ethnic/Racial Minority Adolescents. Issue 3 (3rd April 2019) - Yip, Tiffany; Cheon, Yuen Mi; Wang, Yijie; Cham, Heining; Tryon, Warren; El‐Sheikh, Mona
Abstract : This study investigates the same‐day associations between discrimination and sleep among 350 adolescents ages 13–15 ( M  = 14.29, SD  = 0.65; Asian = 41%, Black = 22%, Latinx = 37%). Assessing sleep duration, sleep onset latency, and wake minutes after sleep onset using wrist actigraphy, Black adolescents slept 35 min less than Asian and 36 min less than Latinx youth. Black adolescents suffered the most wake minutes after sleep onset, followed by Latinx and Asian youth. Latinx youth reported the highest levels of sleep disturbance, whereas Asian youth reported the highest levels of daytime dysfunction. Daily discrimination was associated with lower levels of same‐night sleep onset latency, more sleep disturbance, more next‐day daytime dysfunction, and higher next‐day daytime sleepiness.